Circumstantial Evidence and Unfair Business Competition Practice: Is A Law Reform Necessary? - Salsalina Itha Karina; Ditha Wiradiputra (Sociological Jurisprudence Journal, 2022)
The use of circumstantial evidence in unfair business competition case investigations are regulated institutionally by the Commission for the Supervision of Business Competition. However, due to the absence of regulation as a basis of its use in the Commercial Court and the Supreme Court, this practice remains questionable. This article aims to analyze the issue regarding the use of circumstantial evidence in the Commercial Court and the Supreme Court in order to evaluate the urgency of a law reform to the existing competition law in Indonesia. Based on the research, it was found that there are several issues on the practice, including (1) the absence of a law regarding the use of circumstantial evidence may result in a legal certainty; (2) different views regarding the practice result in inconsistencies in law enforcement; (3) this practice contradicts the principle of the due process model which is adopted in Indonesia. A law that is constructed systematically is necessary to ensure the legal certainty of those who are trying to seek for justice, particularly related to the enforcement of competition law.